Hölderlin's philosophy of nature - Tobias, Rochelle, 1963- (New perspectives in ontology., 2020)
This collection of 15 essays by distinguished international scholars reconsiders what Friedrich Hölderlin's work reveals about the impulses toward form and formlessness in nature and the role that poetry plays in creating Holderlin's 'harmonious opposition'.